Strategically vague - Desmond, Chris (PINS-Psychology in Society, 2025)
Bernstein, J (2013) Violence: Thinking without banisters. Cambridge: Polity Press. ISBN 978-0-7456-7064-5 pbk. Pages ix + 228 As an unidentified dyslexic in primary school I worked my way into the advanced reading group. When a school inspector arrived, conducted a series of tests and declared that I was some rather significant number of years behind in my reading age, my teachers expressed shock. I had fooled them by learning and applying two lessons: the blurb on the back of the book gives you a lot to talk about; and never be too specific, leave what you say open to almost any interpretation, that way you will never be exposed. In reviewing Violence: Thinking without banisters, I am left reflecting on these primary school years. Firstly about just how exposed I would be if I tried to use the blurb on the back of the book to bluff my way through a review (the book itself has little to do with the proposed summary on the back cover). Secondly, I missed my calling, I should have been a philosopher. Apparently if you leave everything you say unspecific and open to interpretation, people speak about you for years after your death – mainly because they are looking for themselves, or at least their ideas, in your non-specific writings.